2016
DOI: 10.1038/srep28634
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced nuclear translocation of CDK5 suppresses neuronal death by downregulating ERK activation via VRK3 phosphorylation

Abstract: Although extracellular signal-related kinase 1/2 (ERK 1/2) activity is generally associated with cell survival, prolonged ERK activation induced by oxidative stress also mediates neuronal cell death. Here we report that oxidative stress-induced cyclin-dependent kinase 5 (CDK5) activation stimulates neuroprotective signaling via phosphorylation of vaccinia-related kinase 3 (VRK3) at Ser 108. The binding of vaccinia H1-related (VHR) phosphatase to phosphorylated VRK3 increased its affinity for phospho-ERK and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…We also found that upregulation of phosphorylated ERK1/2 promotes neuronal survival [18]. In the present study, we found that ERK1/2 phosphorylation is regulated by CDK5 and is inhibited by sevoflurane-induced CDK5 activation, in agreement with a previous report [27]. Activated ERK1/2 can phosphorylate and activate PPARγ and CREB and thereby abrogate sevoflurane-induced, CDK5-mediated neuronal injury.…”
Section: Discussionsupporting
confidence: 81%
“…We also found that upregulation of phosphorylated ERK1/2 promotes neuronal survival [18]. In the present study, we found that ERK1/2 phosphorylation is regulated by CDK5 and is inhibited by sevoflurane-induced CDK5 activation, in agreement with a previous report [27]. Activated ERK1/2 can phosphorylate and activate PPARγ and CREB and thereby abrogate sevoflurane-induced, CDK5-mediated neuronal injury.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies demonstrate that the upregulation of HSPs influences the progression of neurodegenerative disorders5657 and protects against disease-associated toxicity in several neurodegenerative conditions171820. Moreover, recently it has been reported that cyclin-dependent kinase 5-mediated phosphorylation of VRK3 at Ser 108 suppresses oxidative stress-induced prolonged ERK activation and subsequent cell death58. The present study investigated endogenous protective mechanisms mediated by HSP70 and VRK3 against glutamate excitotoxicity-induced neuronal cell death.…”
Section: Discussionmentioning
confidence: 89%
“…To determine the neuroprotective effect of the compound in SHSY5Y cells, we co-incubated the compound with H 2 O 2 for 6 h [22,23]. In all the assays, Vitamin E was added as a positive control in order to compare the antioxidant activity of compound 5 .…”
Section: Resultsmentioning
confidence: 99%